Validation Study of the Subjective Value Inventory in Indonesia - Muh. Ahyar Hamka; Whinda Yustisia (Universitas Ahmad Dahlan, 2026)
This study aimed to adapt the Subjective Value Inventory (SVI) developed by Jared R. Curhan (2006) into the Indonesian language and cultural context. The SVI is designed to measure individuals’ subjective evaluations of the psychological and relational quality of negotiation outcomes. The psychometric properties of the instrument were examined using data collected from 258 participants (M_age = 30.59, SD = 9.31). Data were analyzed using Confirmatory Factor Analysis. The results indicated that the best-fitting measurement model was the refined three-factor SVI model, consisting of 11 items. Convergent validity analysis demonstrated that SVI scores were significantly correlated with trust, subjective disconfirmation, interpersonal justice, informational justice, and outcome satisfaction. Predictive validity analysis further revealed that the Global SVI score significantly predicted willingness to negotiate, with a stronger predictive effect than informational justice and interpersonal justice. In addition, measurement invariance analysis showed that the instrument demonstrated equivalent psychometric properties across male and female groups. These findings support the reliability and validity of the Indonesian version of the SVI as a robust instrument for assessing subjective value in negotiation contexts.